2022
DOI: 10.1111/echo.15424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3 months of treatment with empagliflozin on left ventricle global longitudinal strain and myocardial mechano‐energetic effiency

Abstract: Purpose: Sodium glucose transporter-2 (SGLT-2) inhibitors are employed in the treatment of cardiovascular diseases such as heart failure and coronary artery disease. In the present study, we aimed to investigate how Empagliflozin in SGLT 2 inhibitors affects cardiac contraction and pump efficiency in patients who have Diabetes Mellitus (DM) without cardiovascular disease. Methods:The conventional echocardiographic records and biochemical values of 62 patients who had DM without a history of cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Importantly, in our sample only 31.4% of patients were taking SGLT2 inhibitors, as this drug class was not included in the criteria for optimal care medication for non-diabetic patients, according to the recommendations at the time of patient recruitment [24]. A larger proportion of patients using SGLT2 inhibitors should be included in future trials, given that the existing data show this class's effects on reducing major cardiovascular events in HFrEF [39,40] and their impact on LV reverse remodeling [41,42]. The fact that the TTE scans were carried out by our center's echocardiography staff, which were not blinded to the length of treatment, is another limitation of this study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Importantly, in our sample only 31.4% of patients were taking SGLT2 inhibitors, as this drug class was not included in the criteria for optimal care medication for non-diabetic patients, according to the recommendations at the time of patient recruitment [24]. A larger proportion of patients using SGLT2 inhibitors should be included in future trials, given that the existing data show this class's effects on reducing major cardiovascular events in HFrEF [39,40] and their impact on LV reverse remodeling [41,42]. The fact that the TTE scans were carried out by our center's echocardiography staff, which were not blinded to the length of treatment, is another limitation of this study.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Alslan et al 2 28 demonstrated that empagliflozin may enhance the structure and electrical conductions of the atrium and may prevent T2DM patients from T2DM-related functional disorders and arrhythmias. Recently, Duran et al 2 25 showed that empagliflozin improves the GLS and the myocardial mechanoenergetic efficiency in 62 T2DM patients at 3 months follow-up. Our data confirmed the effect of SGLT2-I on cardiac function in T2DM patients because, in our study, the SGLT2-i therapy improve the subclinical cardiac left ventricular dysfunction, evaluated through LV GLS and MWG, among T2DM patients with baseline preserved LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] To date, some subanalysis of clinical trials evaluated the effect of SGLT2-i therapy on cardiac structure and function in diabetic patients [21][22][23][24] ; however, few real-world studies evaluated the changes in MW parameters following SGLT2-I therapy in T2DM patients. 25 Zhang et al 2 26 in a meta-analysis of 13 randomized control trials involving a mixed population of 1251 T2DM and/or heart failure patients (638 treated with SGLT2-i) showed that SGLT2i treatment significantly reversed cardiac remodeling, improving LV systolic and diastolic function, LV mass and volume, especially in patients with HFrEF and among those taking empagliflozin compared with other SGLT2-i. More recently, Theofilis et al 2 27 in a metaanalysis of 32 studies including 2351 patients showed an improvement in GLS and reduction in E/E' in patients treated with SGLT2-i irrespective of LVEF and presence of HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation